Codon usage bias in yeasts and its correlation with gene expression, growth temperature, and protein structure - Baeza, Marcelo; Sepulveda, Dionisia; Cifuentes, Víctor; Alcaíno, Jennifer (Frontiers in Microbiology, 2024)
Codon Usage Bias (CUB) has been described in viruses, prokaryotes, and eukaryotes and has been linked to several cellular and environmental factors, such as the organism's growth temperature, gene expression levels, and regulation of protein synthesis and folding. Most of the studies in this area have been conducted in bacteria and higher eukaryotes, in some cases with different results.In this study, a comparative analysis of CUB in yeasts isolated from cold and template environments was performed in order to evaluate the correlation of CUB with yeast optimal temperature of growth (OTG), gene expression levels, cellular function, and structure of encoded proteins. Among the main findings, highly expressed ORFs tend to have a more similar CUB within and between yeasts, and a direct correlation between codons ending in C and expression level was generally found. A low correspondence between CUB and OTG was observed, with an inverse correlation for some codons ending in C. The clustering of yeasts based on their CUB partially aligns with their OTG, being more consistent for yeasts with lower OTG. In most yeasts, the abundance of preferred codons was generally lower at the 5' end of ORFs, higher in segments encoding beta strand, lower in segments encoding extracellular and transmembrane regions, and higher in "translation" and "energy metabolism" pathways, especially in highly expressed ORFs.Based on our findings, it is suggested that the abundance and distribution of preferred and nonpreferred codons along mRNAs contribute to proper protein folding and functionality by regulating protein synthesis rates, becoming a more important factor under conditions that require faster protein synthesis in yeasts.Codon usage bias (CUB), Relative synonymous codon usage (RSCU), preferred and non-preferred codons, codon clusters, environmental yeasts.